(untitled) (International Journal of Environmental Sciences, 2025)
The objective of the study was to evaluate the quadratic correlation coefficients obtained from the value of the hydrogen ion potential (pH) of particulate samples (sawdust) of the forest species Aspidosperma polyneuron Müll.Arg (acerillo), Cordia iguaguana Melch. former I.M. Johnst (iguaguana), Licaria triandra (Sw.) Kosterm (latero), Manilkara bidentata subsp. surinamensis (Miq.) T.D. Penn (michino) and Nectandra reticulata (Ruiz & Pav.) Mez (roble), using calcium chloride dihydrate (CaCl2.2H2O) 0,01M and distilled water as extractors, varying their volumes from 50ml, 75 ml, 100 ml, 125 ml and 150 ml, for a sawdust weight of 10 g. The results showed that the lowest average slope was 0.0084 for an average correlation coefficient (R2) of 0,9334 of the pH in the filtrate with 0.01 M CaCl2.2H2O, demonstrating less dependence between the sawdust/extractor ratio. It was also evident that for the extractant CaCl2.2H2O the pH values in the filtrate of the species Aspidosperma polyneuron Müll.Arg, Cordia iguaguana Melch. former I.M. Johnst, Licaria triandra (Sw.) Kosterm, Manilkara bidentata subsp. surinamensis (Miq.) T.D. Penn and Nectandra reticulata (Ruiz & Pav.) Mez, range from 6,97 to 7,00, 7.15 to 7,20, 6,76 to 6,79, 7,04 to 7,07 and 7,08 to 7,11 respectively, concluding that the pH value of the sawdust samples of these species should be carried out in 0,01M CaCl2.2H2O in volumes ranging from 75 ml to 125 ml.